2010
DOI: 10.1113/jphysiol.2010.188367
|View full text |Cite
|
Sign up to set email alerts
|

Substance P inhibits GABAB receptor signalling in the ventral tegmental area

Abstract: Substance P (SP) and its receptors are involved in anxiety-related behaviours and regulate the intake of drugs of abuse and alcohol. Within the midbrain ventral tegmental area (VTA), a region that is clearly involved in the control of these behaviours, SP is released by stress and has been shown to trigger relapse. SP activates neurokinin (NK) receptors, which excites midbrain dopamine (DA) neurons and leads to increased DA in target regions. In this study, we have investigated the mechanisms underlying SP act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Here, we sought to determine potential alterations in (i) the expression of SP and NK-1R in the CeM of dependent compared to naïve rats and (ii) the modulation of GABA transmission by the (10,24). SP/NK-1R interaction has also been associated with noncanonical signaling pathways including activation of AC (22,25), phospholipase A2 (26), or G protein-independent phosphotyrosine kinase-mediated mechanisms (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we sought to determine potential alterations in (i) the expression of SP and NK-1R in the CeM of dependent compared to naïve rats and (ii) the modulation of GABA transmission by the (10,24). SP/NK-1R interaction has also been associated with noncanonical signaling pathways including activation of AC (22,25), phospholipase A2 (26), or G protein-independent phosphotyrosine kinase-mediated mechanisms (27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to determine the intracellular mechanism(s) involved in mediating SP-induced GABA release, we assessed SP (100 nM) effects on sIPSCs in the presence of pharmacological blockers of PLC [5 M U73122 for phosphatidylcholine-specific PLC (PC-PLC) (24) or 10 M D609 for phosphatidylinositol-specific PLC (PI-PLC) ( on CeA GABA transmission (data are summarized in table S1), indicating that SP-induced CeM GABA release is primarily mediated via an interaction with GIRK channels.…”
Section: Sp Mediates Cem Gaba Release Via An Interaction With Inward mentioning
confidence: 99%
“…Typically modulation has been studied on the order of minutes (Xia et al, 2010) to days (Arora et al, 2011). The data presented here show that release of calcium from stores inhibits GIRK currents in milliseconds and reverses in seconds, a dynamic process that can modulate on the timescale of GIRK-dependent synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly proposed mechanism(s) involve protein kinase C (PKC) (Mao et al, 2004). PKC-dependent inhibition has been reported to be either calcium-independent (Stevens et al, 1999; Leaney et al, 2001) or calcium-dependent (Hill and Peralta, 2001; Xia et al, 2010). The inhibition of GIRK by phospholipase C (PLC) has also been shown to be directly (Kobrinsky et al, 2000) and indirectly involved (Keselman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that activation of GPCRs like NK1 can result in reduction of GABA B responsiveness of VTA neurons via PKC (Xia, et al, 2010). The present report is the first to show that such interaction (in this case between GPCRs that both activate GIRKs), can be long-lasting (30 min).…”
Section: Discussionmentioning
confidence: 99%